2007
DOI: 10.4049/jimmunol.178.8.4926
|View full text |Cite
|
Sign up to set email alerts
|

Schnurri-2 Controls Memory Th1 and Th2 Cell Numbers In Vivo

Abstract: Schnurri-2 (Shn-2) is a large zinc-finger containing protein, and it plays a critical role in cell growth, signal transduction and lymphocyte development. In Shn-2-deficient CD4 T cells, the activation of NF-κB was up-regulated and their ability to differentiate into Th2 cells was enhanced. We herein demonstrate that Th1 and Th2 memory cells are not properly generated from Shn-2-deficient effector Th1/Th2 cells. Even a week after the transfer of effector Th1/Th2 cells into syngeneic mice, a dramatic decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In a series of studies on the role of Shn-2 in the CD4 T cell immunity, we have found that Shn-2 is required for the generation of sufficient numbers of both memory Th1 and Th2 cells [42 ]. The expression levels of Shn-2 were high in naïve CD4 T cells, but they were decreased after TCR stimulation, and increased again in memory Th1/ Th2 cells, particularly in memory Th2 cells.…”
Section: Maintenance Of Memory Th2 Cell Numbersmentioning
confidence: 97%
“…In a series of studies on the role of Shn-2 in the CD4 T cell immunity, we have found that Shn-2 is required for the generation of sufficient numbers of both memory Th1 and Th2 cells [42 ]. The expression levels of Shn-2 were high in naïve CD4 T cells, but they were decreased after TCR stimulation, and increased again in memory Th1/ Th2 cells, particularly in memory Th2 cells.…”
Section: Maintenance Of Memory Th2 Cell Numbersmentioning
confidence: 97%
“…The Schnurri family of large zinc-finger proteins consists of three mammalian homologs (Shn1, Shn2, and Shn3) that are present in numerous tissue and cell types, including those within the skeleton (10)(11)(12)(13)(14)(15)(16)(17). Recent analysis of mice deficient in individual Shn genes has uncovered a novel role for this protein family in regulating skeletal remodeling.…”
mentioning
confidence: 99%
“…Schnurri (Shn) family proteins are large zinc-finger containing proteins that regulate morphogenesis in C. elegans and Drosophila 6,7. In vertebrates, they influence bone formation, adipogenesis, and memory T cell survival810. Interestingly, Shn2 −/− mice have very few post-selection DP thymocytes or mature single positive (SP) thymocytes but how Shn2 regulates T cell development has remained a mystery (Fig.…”
mentioning
confidence: 99%